Sistem Analisis Kerusakan Sepeda Motor Karburator dengan Metode Forward Chaining - Zainil Abidin; Deni Erpian (Cakrawala Repositori IMWI, 2021)
Motorcycles are said to be a means of land transfortation that is very popular with many people in the country but also in various parts of the world. In this era of advanced writers become writers on the rapid technology that is very rapid today, the author increasingly ideas for where in one program what is the application of motorcycle carburetor damage system de ngan forward chaining method or often called the application of expert applications into the quality of motorcycle service activities, especially in the workshop in a workshop. The author tried to modify an application that will be a lot of much loved sep eda motor to be able to easily get users more solutions from all solutions experienced by users. Applications that will design whether there is a carburetor motorcycle damage system by forward chaining and using basic visual tools as well as for modeling using UML (Unified Modeling Language) with microsoft access input database.